Vektor Teknik Sipil dengan Pailkem (Pembelajaran Aktif, Inovatif, Lingkungan, Kreatif, Efektif dan Menarik) - Sigamura, Radha Krisnamurti; Nurul, Dhian (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
There are many mathematics learning strategies that educators use to achieve more optimal results. The PAILKEM learning strategy is a learning strategy that makes it possible to achieve learning objectives. The aim of this learning is to improve understanding results. The hypothesis in this research is that there is a significant influence of the PAILKEM learning strategy (Active, Innovative, Environmental, Creative, Effective and Interesting Learning) on ??understanding vector material. This research method uses an experimental method using the True Experimental Design design. Data analysis was carried out using the t-test. The results of the research, after testing the hypothesis using the t-test with a significance level of 0.05, previously carried out a normality test and homogeneity test, obtained tcount > ttable, namely thitnug = 7.636> ttable = 1.6689 so that Ho was rejected and Ha was accepted. The conclusion of this research is that there is an influence of the PAILKEM learning strategy (Active, Innovative, Environmental, Creative, Effective and Interesting Learning) on ??understanding vector material.